Konsep Interaksi Simbolik Dalam Paradigma Sosial - Arsjad, Rasyida (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2017)
Social human beings cannot be separated from the interaction between the individual with others as the form of relationship of cooperation, both in behavior and communication to maintain life in a community. The existence of these interactions create the appearance of special symbols as the manifestation of series of events that occurred between one and the other individual in the community. Implicated symbolic interaction with body movements, physical or vocal sounds, and so forth. Through qualitative method using phenomenology approach or interpretive perspective, the concept of symbolic interaction in the social paradigm to study an individuals actions in the social sphere and the things that shape the social action of the corner of actor (perpetrator). In essence, human play a role as an actor generated by the actions of a conscious and reflective, resulting in an action that implied the truth. Through the concept of symbolic interaction can be concluded that the interaction of individuals through its actions on others in the community as the main factor that distinguishes itself by the animal with superior ethics through action that is human.